SGLT2 inhibition and adipose tissue metabolism: current outlook and perspectives - Cassandra Morciano; Shawn Gugliandolo; Umberto Capece; Gianfranco Di Giuseppe; Teresa Mezza; Gea Ciccarelli; Laura Soldovieri; Michela Brunetti; Adriana Avolio; Amelia Splendore; Alfredo Pontecorvi; Andrea Giaccari; et al. (Cardiovascular Diabetology, 2024)
Abstract Sodium-glucose co-transporter 2 inhibitors (SGLT2i) have emerged as important agents for the treatment of type 2 diabetes mellitus (T2DM). SGLT2 inhibitors have been associated with improved cardiovascular outcomes, not only through their immediate hemodynamic effects—such as glycosuria and (at least temporary) increased natriuresis—but also due to their multifaceted impact on metabolism. Recently, studies have also focused on the effects of SGLT2 inhibitors on adipose tissue. Aside from the well-documented effects on human adiposity, SGLT2i have shown, both in vitro and in murine models, the ability to reduce fat mass, upregulate genes related to browning of white adipose tissue, influence adipocyte size and fatty acid oxidation, and improve oxidative stress and overall metabolic health. In humans, even though data are still limited, recent evidence seems to confirm that the SGLT2i effects observed in cardiovascular outcome trials could be partially explained by their impact on adipose tissue. This review aims to clarify the impact of SGLT2i on adipose tissue, highlighting their role in metabolic health and their potential to transform treatment strategies for T2DM beyond glucose metabolism. Graphical abstract